Competitividad y el potencial de exportación de las empresas de peces ornamentales de la Región Loreto, periodo 2023 - Encinas Matute, Francesca Aneleth (2024)
This thesis focuses on investigating the relationship between competitiveness and export potential of ornamental fish production companies in the Loreto region during the period 2023. The research is based on the premise that competitiveness plays a crucial role in the ability of these companies to participate and thrive in international markets. The methodological framework includes the use of the Spearman test with a 95% confidence level to assess the relationship between competitiveness and export potential. Specific hypotheses related to key aspects such as resources, performance and innovation-value creation have been formulated and evaluated. The results obtained reveal significant findings, confirming the existence of substantial relationships between competitiveness and export potential in Loreto's ornamental fish industry in 2023. These findings offer valuable insights for business actors, policy makers and other stakeholders, highlighting the importance of factors such as resource management, business performance and innovation in driving competitiveness and thus export potential. Despite the achievements, it is recognized that there are limitations to the research in terms of not being able to fully address the external factors that affect long-term customer loyalty. This restriction highlights the inherent complexity of the external elements and underscores the need for future research that delves deeper into these variables to develop more effective strategies for customer retention in the Loreto fishing industry.